Aesthetic Preference for Negatively-Valenced Artworks Remains Stable in Pathological Aging: A Comparison Between Cognitively Impaired Patients With Alzheimer's Disease and Healthy Controls - Kliem, Elisabeth; Forster, Michael; Leder, Helmut (Frontiers in Psychology, 2022)
Background Despite severe cognitive dysfunction in Alzheimer's disease (AD), aesthetic preferences in AD patients seem to retain some stability over time, similarly to healthy controls. However, the underlying mechanisms of aesthetic preference stability in AD remain unclear. We therefore aimed to study the role of emotional valence of stimuli for stability of aesthetic preferences in patients with AD compared to cognitively unimpaired elderly adults. Methods Fifteen AD patients (Mini-Mental State Examination (MMSE) score 12–26) without visual impairment and/or psychiatric disorder, as well as 15 healthy controls without cognitive impairment (MMSE ≥ 27) matched in age, sex, art interest and highest level of education were included in this study. All participants were asked to rank-order eight artworks per stimulus category (positive, negative, neutral in emotional valence) according to their preference twice with a 2-week span in-between. Based on these two rankings a preference change score was calculated. In order to assess explicit recognition memory of the artworks in the second testing session, four artworks of each stimulus category used in the preference ranking task were presented together with a content-matched distractor artwork painted by the same artist. Participants had to indicate which of the stimuli they had seen 2 weeks previously. Results AD patients [MMSE (M) = 18.9 ± 3.6; Age (M) = 85.4 ± 6.9; 33.3% male] had no explicit recognition memory of the artworks (recognition at chance level), whereas healthy controls [MMSE (M) = 27.7 ± 1.4; Age (M) = 84.3 ± 6.7; 33.3% male] correctly recognized 85% of stimuli after 2 weeks. AD patients had equally stable preferences compared to the control group for negative artworks, but less stable preferences for positive and neutral images (Bonferroni-corrected significance levels; p < 0.017). Conclusion Even in cognitively impaired AD patients, aesthetic preference for negatively-valenced artworks remains relatively stable. Our study provides novel evidence that AD patients may have a somewhat preserved implicit valence system for negative compared to neutral or positive visual information, especially in the domain of aesthetics. However, more studies need to further uncover the details of the underlying neurocognitive mechanisms of preference stability in pathological aging.